2004
DOI: 10.1023/b:biom.0000045728.80518.d9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental cadmium exposure and forearm bone density

Abstract: Environmental exposure to cadmium may give rise to osteomalacia combined with renal dysfunction, so called 'Itai-Itai disease', which was endemic in the heavily polluted area in Japan. The main focus of this study was to investigate whether environmental exposure to cadmium is associated with low bone mass in a population living near a smelter. A total of 790 persons (302 males and 488 females), who were all over 35 years old and resided in areas near a lead, zinc and cadmium smelter and in a control area in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 12 publications
2
30
0
1
Order By: Relevance
“…We mainly investigated the relationships between cadmium-associated biomarkers and bone metabolic markers, as well as ultrasonic bone evaluation parameters, because previous studies reported that bone absorption was accelerated by cadmium intake. The other parameters will be investigated in a further study [31][32][33][34][35][36][37][38][39][40][41][42]. Correlation between two substances in urine was calculated from the original measured values, adjusted by age and logarithmic transformed creatinine, while correlations between substances in urine and other parameters were calculated from values in urine corrected by urinary creatinine adjusted by age [43].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We mainly investigated the relationships between cadmium-associated biomarkers and bone metabolic markers, as well as ultrasonic bone evaluation parameters, because previous studies reported that bone absorption was accelerated by cadmium intake. The other parameters will be investigated in a further study [31][32][33][34][35][36][37][38][39][40][41][42]. Correlation between two substances in urine was calculated from the original measured values, adjusted by age and logarithmic transformed creatinine, while correlations between substances in urine and other parameters were calculated from values in urine corrected by urinary creatinine adjusted by age [43].…”
Section: Resultsmentioning
confidence: 99%
“…Several population-based studies showed an association between osteoporosis and environmental cadmium exposure. Zhu and colleagues [39] investigated a population living in an area near a lead, zinc, and cadmium smelter and a population in a control area in southeast China. Forearm bone mineral densities of the participants were measured by SPA-4 single-photon absorptiometry.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical features associated with osteoporosis include increased morbidity (ie, pain, physical impairment, and decreased quality of life), increased risk of new fractures, and increased mortality. (7) Studies among populations from Belgium, (4,8) Sweden, (9)(10)(11) Japan, (12) and China (13,14) showed associations between osteoporosis and low-level environmental cadmium exposure. The generally accepted interpretation has been that cadmiuminduced renal tubular damage (2) decreases the calcium reabsorption in the nephron, resulting in hypercalciuria (2) and low BMD and hence increased fracture risk, (4,11) particularly in postmenopausal women (4,8) or men in the older age group.…”
Section: Discussionmentioning
confidence: 99%
“…Cadmium can cause renal tubular dysfunction, decrease bone mineral density, and cause hypercalciuria, all factors that can increase risk of fracture, osteomalacia, and osteoporosis [44][45][46][47][48][49]. Although cadmium toxicity affects both genders, elderly females are more susceptible than men, especially after menopauses [50][51][52][53].…”
Section: Cadmiummentioning
confidence: 99%